Strategi Penguatan UMKM dan Literasi Keuangan Syariah di Desa Tanjung Gusta melalui Promosi Digital - Nadia Aswana; Khasanah Khairiyyah; Evicenna Yuris (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to identify and analyze the strategies for strengthening Micro, Small, and Medium Enterprises (MSMEs) and sharia financial literacy in Tanjung Gusta Village through the implementation of digital promotion. The village has many untapped MSME potentials, with major challenges in market access and sharia financial understanding. Digital promotion and sharia financial literacy training were provided to business owners to enhance their ability to expand market reach and manage finances according to sharia principles. The research method used includes observation, in-depth interviews, and case studies. The results indicate that the implementation of digital promotion through social media significantly increased MSME product visibility, while sharia financial literacy helped business owners improve financial management, reduce consumptive behavior, and avoid financial risks that are not aligned with sharia principles. This strategy is considered effective in strengthening MSMEs and empowering the community in a sustainable manner.